Transient neonatal diabetes mellitus caused by a novel mutation in the ABCC8 gene - Unal, Edip; Yıldırım, Ruken; Taş, Funda Feryal; Yıldız, Süleyman; Demir, Vasfiye; Haspolat, Yusuf Kenan (Journal of Surgery and Medicine, 2019)
Neonatal diabetes mellitus is a rare monogenic form of diabetes that develops in the first 6 months of life. Neonatal diabetes mellitus is commonly divided in two groups as transient and permanent. Genetic and epigenetic anomalies of chromosome 6q24 locus are responsible for 70% of transient neonatal diabetes mellitus cases. Incidence of macroglossia, umbilical hernia, cardiac and renal anomalies is increased in transient neonatal diabetes mellitus patients. Mutations in the genes (ABCC8 and KCNJ11) encoding two protein subunits (SUR1 and Kir6.2) of ATP-sensitive potassium channels constitute the second common cause of transient neonatal diabetes mellitus. In this article, we present a case with homozygous missense mutation (DNA expression: c1456> T), which was found in the ABCC8 gene in a 3.5-month-old patient with no congenital anomalies, leading to transient neonatal diabetes mellitus.